Power configuration in the Muslim world: exploring the post-WWII Era - Quddus, S. M. Abdul (Springer, 2012)
This chapter analyzes the features, trends, and issues related to governmental systems, conflicts and coercion, competition and imposition, and so on in the Muslim majority countries (MMCs). The chapter looks at the styles of governments in the MMCs, and shows how the ‘patrimonial’ authoritarian governments in the MMCs promote ‘clientelism’ resulting in ‘syncretic’ politics of coercion and conflicts. It suggests that many MMCs by virtue of their authoritarian (semiauthoritarian or semidemocratic) government style suffer from conflicts between landed aristocracy and rising industrialists, patron–client politics, ‘executive dominance’; and a symbiotic relationship between the military, bureaucracy, and the business elites. The chapter concludes that these factors resulting from external influences and relationships and the built-in institutional difficulties shape power relationships and governance pattern in the MMCs to hamper human development and need to be dealt with diligently for improvements in human development.